Interaction of Biliverdin Chromophore with Near-Infrared Fluorescent Protein BphP1-FP Engineered from Bacterial Phytochrome - Stepanenko, Olesya V. (Int J Mol Sci, 2017)
Near-infrared (NIR) fluorescent proteins (FPs) designed from PAS (Per-ARNT-Sim repeats) and GAF (cGMP phosphodiesterase/adenylate cyclase/FhlA transcriptional activator) domains of bacterial phytochromes covalently bind biliverdin (BV) chromophore via one or two Cys residues. We studied BV interaction with a series of NIR FP variants derived from the recently reported BphP1-FP protein. The latter was engineered from a bacterial phytochrome RpBphP1, and has two reactive Cys residues (Cys15 in the PAS domain and Cys256 in the GAF domain), whereas its mutants contain single Cys residues either in the PAS domain or in the GAF domain, or no Cys residues. We characterized BphP1-FP and its mutants biochemically and spectroscopically in the absence and in the presence of denaturant. We found that all BphP1-FP variants are monomers. We revealed that spectral properties of the BphP1-FP variants containing either Cys15 or Cys256, or both, are determined by the covalently bound BV chromophore only. Consequently, this suggests an involvement of the inter-monomeric allosteric effects in the BV interaction with monomers in dimeric NIR FPs, such as iRFPs. Likely, insertion of the Cys15 residue, in addition to the Cys256 residue, in dimeric NIR FPs influences BV binding by promoting the BV chromophore covalent cross-linking to both PAS and GAF domains.